(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Currently, the prevention and elimination of the causes of global environmental disasters depends on the environmental consciousness in society, and its appropriate formation is one of the urgent problems facing the educational system.